Clinical and radiographic outcomes of lateral sinus augmentation using a controlled osteotomy strategy: an analytical retrospective observational study - Jung-Tae Lee; Bongju Kim; Yong-Gun Kim; Sungtae Kim (BMC Oral Health, 2026)
Abstract Background Lateral sinus augmentation is a widely used procedure for implant placement in the posterior maxilla with insufficient residual bone height. This study retrospectively described the clinical and radiographic outcomes of lateral sinus augmentation performed using a controlled osteotomy strategy, referred to as the Wedge and Feather (WF) technique, and explored factors potentially associated with vertical bone gain. Methods This descriptive retrospective case series included consecutive patients who underwent lateral sinus augmentation using the WF technique. Clinical and radiographic data were collected from routine records. Vertical bone gain and complication rates were summarized descriptively. Because of the small sample size and absence of a control group, inferential analyses were considered exploratory and hypothesis-generating. Results A total of 38 patients (43 sinus augmentation sites, 55 implants) was included. The mean vertical bone gain measured on postoperative panoramic radiographs was 8.5 ± 2.3 mm (range: 3.8–13.3 mm). Schneiderian membrane perforation occurred in 2 sites (4.7%), intraoperative bleeding in 1 site (2.3%), and postoperative sinusitis in 3 sites (7.0%). No implant failure was observed during the available follow-up period; however, no formal survival analysis was performed. Conclusion Because this retrospective case series lacked a control group and postoperative bone gain was measured using panoramic radiographs rather than CBCT, the findings should be interpreted as descriptive and hypothesis-generating. The WF technique was associated with clinically manageable surgical complications and radiographic bone gain in this single-surgeon cohort, but no conclusions regarding superiority or non-inferiority relative to conventional rotary or piezoelectric techniques can be drawn.